1991
DOI: 10.1007/bf00191087
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic findings of degeneration in cervical spines of middle-aged soccer players

Abstract: Twelve amateur veteran soccer players (average age 40.1 +/- 5.4 years), who began playing in their teens and who were admitted with symptoms most likely to be related to cervical spondylosis, were examined by cervical radiography. Abnormal radiographic findings included: calcification of anterior longitudinal ligament (25%), anterior (75%) and posterior vertebral spurs (75%), ossicle between spinous processes (75%), calcification of nuchal ligament (Barsony) (58%), ossicle on spinous process (25%), and bony sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…10 It is also noteworthy that a Japanese study found cervical osteophytes in 9 of 12 players who made extensive head plays. 8 The sumo wrestlers in our study had the same or greater rates of cervical degenerative changes compared with the athletes in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 53%
“…10 It is also noteworthy that a Japanese study found cervical osteophytes in 9 of 12 players who made extensive head plays. 8 The sumo wrestlers in our study had the same or greater rates of cervical degenerative changes compared with the athletes in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 53%
“…It is also noteworthy that a Japanese study found cervical osteophytes in 9 of 12 soccer players making head plays intensively. 38 These osteophytes are the consequence of a previously described constraint phenomena. 14,67 Forces placed on the cervical spine often exceed its physiologic limits.…”
Section: Discussionmentioning
confidence: 94%
“…Such a co-existence would produce pressure on the spinal cord and may make soccer players more susceptible to neurological complications. Abnormal radiological findings have been described in amateur veteran soccer players [11], however, biomechanical studies or advanced diagnostic evaluation using magnetic resonance (MR) were not carried out to quantify degeneration and existing pathologies.Abstract Background. Radiological changes and degeneration of the cervical spine have been previously described in soccer players.…”
mentioning
confidence: 99%